Preliminary results from a study of habitat use of radio-tracked Spotted Crakes Porzana porzana at a restored wetland in northeast Jutland, Denmark - Fox, Anthony D.; Desholm, Mark; Rasmussen, Palle A.F.; Balsby, Thorsten J.S. (Wildfowl, 2013)
Singing Spotted Crakes Porzana porzana were surveyed across c.16 km2 of restored peatÂ cuttings in Lille Vildmose, northern Jutland, Denmark during summer 2013. MappingÂ of singing birds on 16 nights between 16 April and 9 July confirmed nine occupiedÂ â€œterritoriesâ€ based on the presence of between 0â€“6 birds on any one date. SingingÂ Spotted Crakes were associated with shallower parts of peat extraction areas and flatÂ restored areas with shallow (> 40 cm) water and dense vegetation. Singing birds wereÂ never heard in deep water channels, raised mire, dry peat cuttings, deep water peatÂ cuttings, restored pasture, arable fields, dense willow carr or dense reed beds. FourÂ radio-tagged Spotted Crakes (two males and a pair) were tracked from late May to earlyÂ August during which time they exploited core home ranges of 0.33â€“0.56 ha.Â Vegetation samples within and around these home ranges showed crakes were presentÂ in most of the wetland vegetation types present, excluding very dry restored grazedÂ grassland, areas dominated by Purple Moor-grass Molinia caerulea and Soft Rush JuncusÂ effusus/Flote-grass Glyceria fluitans wet acidic grassland. In each of the areas used byÂ tagged birds, quadrats within the minimum convex polygons plotted for each radiotaggedÂ individual had deeper standing water than those that were not used, butÂ because of the variation in water levels between the three areas, they did not select forÂ specific water depths across sites. There were no differences in the extent of openÂ water, bare mud, dead vegetation or vegetation height between areas used and not usedÂ by tagged individuals. We conclude that shallow water retained throughout theÂ summer is the most important feature of sites frequented by Spotted Crakes, with theÂ depth of water and vegetation type/height being of secondary importance.